BOND STRENGTH OF THREE ADHESIVE SYSTEMS USED FOR BONDING ORTHODONTIC BRACKETS - Sorana Maria Bucur; Dorin Cocoș; Alina Saghin (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study. The purpose of this study was to compare the bonding force made by three different orthodontic adhesives: Fuji Ortho LC, Ketac Cem conventional and Transbond Plus Color Change Adhesive between metal brackets and tooth enamel. Material and methods. The study was performed in vitro, on a group consisting of 30 maxillary and mandibular premolars extracted for orthodontic purposes. The research group was equally divided in three; on each of those three formed batches metal brackets were bonded, using one of the three different adhesive systems mentioned above. Then, a universal testing machine was used for debonding the brackets. We determined and compared the strength of those adhesive systems by statistical means. Results. The bond strength of Fuji Ortho LC group was greater than that created by using the other two adhesive systems, but clinically acceptable bond strengths were found even for the other two study groups.